Effectiveness of Education on Clean and Healthy Living Behavior through Educational Video - Yunita, Astri; Liya Ni’matul Maula; Erni Rahmawati (HealthCare Nursing Journal, 2025)
The modernization of today's lifestyle has created a trend in the lives of the population in Indonesia. Media as an information channel is one of the important components in health education. The purpose of the study was to determine the effectiveness of education about clean and healthy living behavior on adolescent’s healthy behavior through educational videos. The research sample was students at STIKes Bhakti Mulia semester 1, with purposive sampling, a total of 40 respondents. The research was conducted by giving a pretest and posttest after treatment. The data source was taken from primary data with a research instrument in the form of a healthy behavior questionnaire. Data analysis using the SPSS for window program, data analysis with univariate and bivariate using paired t samples. The results showed that the mean healthy behavior before education was 24.48, then increased after education by 30.50. Based on the paired t test, the p-value is 0.000, this means that there is a significant difference in the healthy behavior of adolescents before and after being given education on clean and healthy living behavior through videos. The conclusion is that education about clean and healthy living behavior through educational videos is effective in improving adolescents' clean and healthy living behavior.